(untitled) (Journal of the College of Basic Education, 2026)
The research aims to identify self-censorship among female students in the kindergarten department and to identify self-censorship among female students in the kindergarten department according to the academic stage. The researcher used the descriptive correlational approach, and the sample consisted of (400) female students from the kindergarten department. A scale was prepared according to Snyder’s theory of self-censorship consisting of (40) items. Using appropriate statistical methods, the research reached the following results: Female students in the kindergarten department enjoy self-censorship, and there are no statistically significant differences in self-censorship between the academic stages.